MEDIA PENYULUHAN PENCEGAHAN DAN PENULARAN VIRUS HIV/AIDS PADA WARIA DAN HOMOSEKSUAL DI LEMBAGA KESEHATAN NAHDLATUL ULAMA (LKNU) JAMBI - Sri Mulyati; Rita Yuliana (JURNAL AKADEMIKA)
Multi-media application is used as a medium of education that provide information about prevention and transmission of HIV / AIDS virus in transsexuals and homosexuals. The author designed a media outreach prevention and transmission of HIV / AIDS among transvestites and homosexuals in the city of Jambi using Adobe Flash CS3 and Adobe Photoshop software support. Disease Human Immunodeficiency Virus (HIV) and Acquired Immunodeficiency Syndrome (AIDS) is a disease that is widespread among people in the world. In Indonesia, the population contract cases of HIV / AIDS is very high, since 1999-2015, the reported cases are of approximately 400,000 and in Jambi was as many as 1,349 people. So that now, HIV / AIDS cases is increasing from year to years.Our goal of this research is to reduce the spread of HIV / AIDS in Jambi and add insight and knowledge about HIV / AIDS to transvestites and homosexuals in the city of Jambi and facilitate Health Organization Nahdlatul Ulama (LKNU) in conducting counseling.